Sleep Bruxism in a Child with Sleep Disturbances and Psychosocial Factors: A Multidisciplinary Case Report - Cut Meutia Fitriani; Arlette Suzy Setiawan (Maranatha Christian University, 2025)
Introduction: Sleep bruxism (SB) is a parafunctional activity of the masticatory muscles characterized by clenching or grinding of the teeth during sleep. In children, SB may lead to severe tooth attrition, restoration failure, and impaired sleep quality, often influenced by psychosocial factors. Early and multidisciplinary intervention is crucial to prevent further oral and functional complications. Methods: This case report describes the comprehensive management of a child diagnosed with severe sleep bruxism. Clinical and radiographic examinations were conducted, and the Children’s Sleep Habits Questionnaire (CSHQ – Abbreviated) was administered to assess sleep quality and behavioral patterns. Dental management included restorative treatment and occlusal protection, combined with sleep hygiene education and family counseling. Case Report: A 5-year-old girl presented with a damaged and dislodged bioflex crown, accompanied by severe attrition of the maxillary and mandibular anterior teeth. Conclusion: Severe sleep bruxism in children requires a multidisciplinary approach addressing dental, behavioral, and psychosocial factors. SSC restoration, acrylic occlusal splint, and sleep hygiene education proved effective in protecting dentition and improving the patient’s sleep and well-being.